Assessing the predictability of an improved ANFIS model for monthly streamflow using lagged climate indices as predictors - Ehteram M.; Afan H.A.; Dianatikhah M.; Ahmed A.N.; Fai C.M.; Hossain M.S.; Allawi M.F.; Elshafie A. (MDPI AG, 2023)
Climate models; Climatology; Fuzzy neural networks; Fuzzy systems; Genetic algorithms; Mean square error; Particle swarm optimization (PSO); Principal component analysis; Stream flow; Adaptive neuro-fuzzy inference system; ANFIS-PSO; Climate index; Confidence levels; ENSO; Probability spaces; Root mean square errors; Streamflow simulations; Fuzzy inference; assessment method; El Nino-Southern Oscillation; genetic algorithm; index method; model; prediction; seasonal variation; streamflow; uncertainty analysis